2016
DOI: 10.1038/srep28116
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferation of berberine is mediated by epigenetic modification of constitutive androstane receptor (CAR) metabolic pathway in hepatoma cells

Abstract: Constitutive androstane receptor (CAR) regulates hepatic xenobiotic and energy metabolism, as well as promotes cell growth and hepatocarcinogenesis. Berberine is an ancient multipotent alkaloid drug which derived from Coptis chinensis plants. Here we report that berberine is able to be cellular uptake and accessible to chromatin in human hepatoma HepG2 cells. Berberine induces more apoptosis, cell cycle arrest, but less ROS production in CAR overexpressed mCAR-HepG2 cells. Moreover, berberine inhibits expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Regarding the mechanisms underlying the downregulation of the CYP3A4 gene, the expression of the CYP3A4 gene was regulated by nuclear receptors, wellestablished xenobiotic sensors capable of binding to various structurally diverse chemicals, such as pregnane X receptor (PXR) (30) and constitutive androstane receptor (CAR) (30,31). Promoter hyper-methylation has been reported to result in repression of CAR and PXR expression, which induces the down-regulation of drug-metabolizing enzymes, including the CYP3A4 gene, in human pluripotent stem cellderived hepatocyte-like cells (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the mechanisms underlying the downregulation of the CYP3A4 gene, the expression of the CYP3A4 gene was regulated by nuclear receptors, wellestablished xenobiotic sensors capable of binding to various structurally diverse chemicals, such as pregnane X receptor (PXR) (30) and constitutive androstane receptor (CAR) (30,31). Promoter hyper-methylation has been reported to result in repression of CAR and PXR expression, which induces the down-regulation of drug-metabolizing enzymes, including the CYP3A4 gene, in human pluripotent stem cellderived hepatocyte-like cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval for all experimental protocols and study was obtained from the institutional review board at the Shizuoka Cancer Center (Authorization Number: [25][26][27][28][29][30][31][32][33]. Written informed consent was obtained from all patients enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…279 Hence, great attention has been focused on compounds that produce inhibitory effects on the NF-κB pathway. Demethyleneberberine (164) reduced inflammatory responses by inhibiting the NF-κB pathway and regulating the balance of Th cells. 280 Chelidonine (300) also significantly inhibited NF-κB activity and related pathways, such as the TLR4/NF-κB signaling pathway, at concentrations of 5-20 μM in HCT116 cells and RAW264.7 macrophages, 281 and it did not display cytotoxic effects with concentrations up to 20 μM.…”
Section: Anti-inflammatory and Immunosuppressive Activitiesmentioning
confidence: 99%
“…[160][161][162][163] The potential targets also include mitochondrial function, DNA topoisomerase and arylamin Nacetyltransferase activity, Nuclear transcription factor-κB (NF-κB) signal pathway, the EGF and the VEGF receptors, and so forth. In human hepatoma cells, the alkaloid's antiproliferative effect might be mediated via the CAR metabolic and the arachidonic acid pathways, cPLA 2 , COX-2 gene expression and mitochondria-mediated apoptosis also were suppressed in vitro and in vivo, [164][165][166] Lycorine 321 Reports indicated that berberine mediates epigenetic reprogramming via HDAC inhibition and regulates Bcl-2/ Bax family proteins in the human lung cancer A549 cell line. 171 Furthermore, it inhibited the growth of intestinal polyps in animals and patients with familial adenomatous polyposis and cell growth in colon cancer by downregulating β-catenin signaling via binding RXRα.…”
Section: Various Isoquinoline Alkaloidsmentioning
confidence: 99%
“…Berberine can increase the expression of MTTP by decreasing the methylation of the promoter of MTTP, thus improve NAFLD [19,20]. Berberine exerts antiproliferation of HepG2 cells by decreasing the methylation of the promoter of CYP2B6 and CYP3A4 on the constitutive androstane receptor (CAR) pathway [21]. Berberine could also increase the expression of the human mutL homolog 1 (hMLH1) by increasing the demethylation of the promoter of hMLH1 [22].…”
Section: The Roles Of Natural Compounds In Regulating Dna Methylationmentioning
confidence: 99%